Reproductive justice: A radical framework for researching sexual and reproductive issues in psychology. Issue 6 (12th May 2021) - Morison, Tracy
Abstract: The reproductive justice framework holds much promise for guiding research that can contribute to social change. Its limited integration and use in social psychology therefore represents a missed opportunity for justice‐oriented social researchers. The purpose of this article is to provide an overview of the reproductive justice framework and demonstrate its value for social psychologists studying sexual and reproductive issues. Using the example of contraceptive provision, rights‐based sexual and reproductive health research is contrasted with reproductive justice‐oriented research to demonstrate how a reproductive justice lens can extend the analytical focus to illuminate the complex roots of an issue. This is crucial for developing policy and interventions that contribute toward longer‐term systemic change and, ultimately, social transformation.